1998
DOI: 10.1094/pdis.1998.82.3.311
|View full text |Cite
|
Sign up to set email alerts
|

Mixed Infection of Hard Red Winter Wheat with High Plains Virus and Wheat Streak Mosaic Virus from Wheat Curl Mites in Nebraska

Abstract: A new disease of wheat and corn caused by the High Plains virus (HPV) has been observed in the High Plains region of western United States. HPV is transmitted by the wheat curl mite, Aceria tosichella, which is also the vector of wheat streak mosaic virus (WSMV). In the field it is extremely difficult to visually differentiate plants infected with WSMV from those with HPV. An indirect protein-A sandwich enzyme-linked immunosorbent assay (PAS-ELISA) and Western blot analysis were used to identify WSMV and HPV. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
27
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 12 publications
2
27
0
Order By: Relevance
“…WSMV and HPV, the two viruses known to be transmitted by WCMs before TriMV's discovery, are widespread in the Great Plains (8,16). Recent studies have shown that co-infection of wheat with WSMV and TriMV results in synergism that increases symptom severity, elevates titers of both viruses (26), and exacerbates biomass and yield loss (2,28).…”
mentioning
confidence: 99%
“…WSMV and HPV, the two viruses known to be transmitted by WCMs before TriMV's discovery, are widespread in the Great Plains (8,16). Recent studies have shown that co-infection of wheat with WSMV and TriMV results in synergism that increases symptom severity, elevates titers of both viruses (26), and exacerbates biomass and yield loss (2,28).…”
mentioning
confidence: 99%
“…HPV was identiÞed from wheat and corn throughout the Great Plains in the mid-1990s Lane 1994, Jensen et al 1996), and TriMV was recently identiÞed from wheat in Kansas (Seifers et al 2008). Because the wheat curl mite transmits all of these viruses, they are often found together in mixed infections in the Þeld (Mahmood et al 1998, Seifers et al 2008. The extent of the interaction of the viruses is not known; however, it is clear that where one or more viruses are present, the resulting disease complex signiÞcantly impacts wheat (Tatineni et al 2010, Byamukama et al 2012.…”
mentioning
confidence: 99%
“…Symptoms caused by WSMV infection can be confused with chlorotic symptoms caused by nutritional deficiencies and certain pest infestations (Shahwan and Hill 1984). Moreover, WSMV infection may occur in combination with other wheat viruses such as BYDV, the High Plains virus, or Agropyron mosaic virus (Montana et al 1994;Mahmood et al 1998). This might confuse the detection of WSM symptoms both in the greenhouse and the field.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the symptoms caused by WSMV can be indistinguishable from chlorosis arising from nutritional deficiency, other viral pathogens and certain pest infestations (Shahwan and Hill 1984;Montana et al 1994;Mahmood et al 1998). Moreover, narrow and dark pigmented leaves often appear in seedlings of wild relatives of wheat as well as their amphiploids, making it difficult to visually assess WSM symptoms (Stoddard et al 1987b).…”
Section: Introductionmentioning
confidence: 99%